Projeto de um sistema hidráulico para um vagão misturador agropecuário - Santos, Jocimar Padilha dos (2023)
The implements used in agriculture, highlighting among them the mixing wagons, which have great applicability, help producers in carrying out their activities, which, in the vast majority of cases, were performed manually, but are now being replaced by systems. mechanical and hydraulic systems, reducing labor, performing several tasks simultaneously in a short period of time. This evolution is extremely necessary, considering that for a good profitability and sustainability of the properties, it is necessary a correct planning and handling of the animals' diets, so that with this a higher daily milk average is reached, or animal weight in the case of cutting confinement. For these equipment to be durable, efficient and meet daily needs, they must be sized correctly. The main objective of this work is the dimensioning of the hydraulic system for an agricultural mixer wagon. During the bibliographical review, topics will be addressed that allow the development and knowledge of technical information about the mixing car, knowledge of the function of each hydraulic component used in the project, as well as the respective equations used for sizing.